Multi-sensor and multi-temporal approach in monitoring of deformation zone with permanent monitoring solution and management of environmental changes: A case study of Solotvyno salt mine, Ukraine - Pukanská, Katarína; Bartoš, Karol; Bakoň, Matúš; Papčo, Juraj; Kubica, Lukáš; Barlák, Ján; Rovňák, Martin; Kseňak, Ľubomír; Zelenakova, Martina; Savchyn, Ihor; Perissin, Daniele (Frontiers in Earth Science, 2023)
Salt deposits were a rich source of mineral resources in the past, and some are still mined today. However, salt mines, especially abandoned ones, pose a threat to populated areas, infrastructure and the natural environment. Solotvyno (Ukraine) is one of the most significantly affected areas, with a deformation zone where significant year-on-year subsidences occur. Mining activities have caused a disturbance of the balance in the mountain massif, and as a consequence, the mountains are being reshaped, and the land cover is deformed. Deformation zone of the historical salt mine Solotvyno (Ukraine), Tyachiv district of Zakarpattia region is situated on the right bank of the Tisza river in the border area with Romania in Central Europe. This paper deals with the multi-sensor monitoring of the active deformation zone over the Solotvyno salt mine using satellite radar data (Sentinel-1), optical satellite imagery (Pleiades, SPOT) and in-situ UAV photogrammetry. Since the area represents a significant geohazard from a hydrogeological (Tisza River) and civil security standpoints (infrastructure of the inhabited regions), the design of a high-precision monitoring system to monitor and evaluate current environmental changes is proposed. Multi-temporal InSAR analysis exposed steeper subsidence tendencies of >-2 cm in the central part of the monitored area. Optical satellite and UAV images confirmed the increase in water surface in sinkhole areas up to 28,500 m2 and proved the emergence of new sinkholes in the central part of the Solotvyno mine. The aim of this study is to describe the post-collapse deformation processes by Pleiades and SPOT multi-spectral sensors and Sentinel-1 satellite SAR sensors since the 2010 collapse in order to describe the trends of deformation due to undermining and propose a high-precision permanent monitoring system based on satellite radar interferometry (InSAR).